Monitoring Shallow Infiltration in Sandy Soil Using GPR Groundwave Techniques - Kristoff, Michael; Mohr, Audrey; Benda, Anya; Crist, Taylor (My University, 2011)
Characterizing the near-surface soil water content distribution is important for precision agriculture and groundwater remediation applications. Measuring soil water content over large areas is often difficult, as conventional point measurement and remote sensing techniques are often insufficient to characterize water content heterogeneity at the field scale. Ground penetrating radar (GPR) groundwaves are an electromagnetic geophysical technique that can be used to estimate water content quickly over large areas. The objective of this field-scale research is to explore the potential of multi-frequency GPR groundwave data for detecting changes in soil moisture at different depths as water moves through the near-surface soil.
Color poster with text, diagrams, images, and tables.
Keywords: Hydrology--Measurement; Soil moisture--Measurement; Ground penetrating radar; Posters